Five new species of the pelodryadid genus Litoria Tschudi from the southern versant of Papua New Guinea’s Central Cordillera, with observations on the diversification of reproductive strategies in Melanesian treefrogs - Richards, Stephen J.; Donnellan, Stephen C.; Oliver, Paul M. (Zootaxa, 2023)
New Guinea has the most diverse insular frog fauna in the world, and rates of species discovery and description have increased rapidly in the last two decades. Pelodryadid treefrogs are the second most diverse family of anurans on the island but their taxonomy, relationships, and especially ecology remain poorly documented. Based on differences in morphology, advertisement calls (where available) and phylogenetic analyses of a 787 base pair alignment from the mitochondrial ND4 gene and flanking tRNA, we describe five new species of small treefrogs from hill and lower montane forests in the high rainfall belt that straddles the southern versant of Papua New Guinea’s Central Cordillera. Three of these species are known only from forest growing on karst substrates, adding to the growing number of herpetofauna species currently known only from the extensive karst habitats of Papua New Guinea’s South-fold Mountains. We also describe the arboreal breeding strategies of two of the new species, and report obligate treehole (phytotelm) breeding in New Guinean frogs for the first time. The new phytotelm–breeding species has juveniles with colour and patterning that closely resemble bird droppings, suggesting defensive mimicry or masquerade. A preliminary phylogeny suggests that arboreal-breeding frogs do not form a monophyletic group and that arboreal breeding has evolved multiple times within the New Guinean pelodryadid radiation. A further striking feature of the phylogeny is poor support for most basal nodes in the most diverse radiation of Melanesian Pelodryadidae, suggesting rapid ecological diversification and speciation, potentially following colonisation from Australia and/or mountain uplift. These new taxa and observations highlight previously unrecognised ecological and reproductive diversity in the Melanesian Pelodryadidae.